Energy transfer in the Congo deep-sea fan: From terrestrially-derived organic matter to chemosynthetic food webs. (August 2017) - Pruski, A.M.; Decker, C.; Stetten, E.; Vétion, G.; Martinez, P.; Charlier, K.; Senyarich, C.; Olu, K.
Abstract: Large amounts of recent terrestrial organic matter (OM) from the African continent are delivered to the abyssal plain by turbidity currents and accumulate in the Congo deep-sea fan. In the recent lobe complex, large clusters of vesicomyid bivalves are found all along the active channel in areas of reduced sediment. These soft-sediment communities resemble those fuelled by chemoautotrophy in cold-seep settings. The aim of this study was to elucidate feeding strategies in these macrofaunal assemblages as part of a greater effort to understand the link between the inputs of terrestrially-derived OM and the chemosynthetic habitats. The biochemical composition of the sedimentary OM was first analysed in order to evaluate how nutritious the available particulate OM is for the benthic macrofauna. The terrestrial OM is already degraded when it reaches the final depositional area. However, high biopolymeric carbon contents (proteins, carbohydrates and lipids) are found in the channel of the recent lobe complex. In addition, about one to two thirds of the nitrogen can be assigned to peptide-like material. Even if this soil-derived OM is poorly digestible, turbiditic deposits contain such high amounts of organic carbon that there is enough biopolymeric carbon and proteacinous nitrogen to support dense benthic communities that contrast with the usual depauperate abyssal plains. Stable carbon and nitrogen isotopes and fatty acid biomarkers were then used to shed light on the feeding strategies allowing the energy transfer from the terrestrial OM brought by the turbidity currents to the abyssal food web. In the non-reduced sediment, surface detritivorous holothurians and suspension-feeding poriferans rely on detritic OM, thereby depending directly on the turbiditic deposits. The sulphur-oxidising symbiont bearing vesicomyids closely depend on the reprocessing of OM with methane and sulphide as final products. Their carbon and nitrogen isotopic signatures vary greatly among sites and could reflect the intensity of the anaerobic oxidation of methane (AOM) in the sediments. Within the vesicomyid habitats, the heterotrophic fauna exhibits a distinctively light carbon isotopic signature in comparison to the background sediments, clearly indicating the utilisation of chemosynthetically-derived OM. Fatty acid biomarkers further confirm that dorvilleid polychaetes consume aggregates that perform AOM. Terrestrial OM reprocessing by microbial consortium thus ensures its transfer to the benthic food web in the Congo deep-sea fan.